2008
DOI: 10.1002/jcp.21392
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism transition in multi‐cellular human tumor spheroids

Abstract: It is thought that glycolysis is the predominant energy pathway in cancer, particularly in solid and poorly vascularized tumors where hypoxic regions develop. To evaluate whether glycolysis does effectively predominate for ATP supply and to identify the underlying biochemical mechanisms, the glycolytic and oxidative phosphorylation (OxPhos) fluxes, ATP/ADP ratio, phosphorylation potential, and expression and activity of relevant energy metabolism enzymes were determined in multi-cellular tumor spheroids, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 73 publications
3
104
0
Order By: Relevance
“…They have been investigated in the contexts of experimental radiotherapy, photodynamic treatment, hyperthermia, and target specific chemotherapy and immunotherapy. [10][11][12][13][14] Moreover, recent studies have shown that the gene expression profiles, 15,16 growth kinetics and metabolic rates 16 of MCTSs are similar to clinical conditions and hence, are believed to mimic in vivo solid tumors in their response to new drug targets and immunological factors. Therefore, MCTSs could help eliminate less efficient cancer drugs and therapies in earlier stages of testing before they enter expensive animal testing, and promote innovative drug targets that would otherwise fail in the traditional drug screening assays.…”
Section: Introductionmentioning
confidence: 99%
“…They have been investigated in the contexts of experimental radiotherapy, photodynamic treatment, hyperthermia, and target specific chemotherapy and immunotherapy. [10][11][12][13][14] Moreover, recent studies have shown that the gene expression profiles, 15,16 growth kinetics and metabolic rates 16 of MCTSs are similar to clinical conditions and hence, are believed to mimic in vivo solid tumors in their response to new drug targets and immunological factors. Therefore, MCTSs could help eliminate less efficient cancer drugs and therapies in earlier stages of testing before they enter expensive animal testing, and promote innovative drug targets that would otherwise fail in the traditional drug screening assays.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the notion that mitochondrial functions such as oxidative phosphorylation become dysregulated in the neoplastic condition. [32][33][34][35][36][37][38][39] VOPP1 overexpression in neoplasia may function to somehow neutralize ROS that form as a by-product of dysregulated mitochondrial function, potentially through the vesicular structures to which this protein has been localized. 3 supported by a gift provided to the University of Virginia by Philip Morris (PM) USA.…”
Section: Ros Are Required For Apoptosis In Scc Cells Induced By Vopp1mentioning
confidence: 99%
“…A significant drop in breast tumor standardized uptake value, however, may occur late in the treatment, by the end of the first cycle of chemotherapy (31) and as early as 8 d after treatment in responders (32). The mechanisms contributing to the delay of 18 F-FDG response are still far from clear, but may be attributed to the unique metabolic plasticity of the regeneration of adenosine triphosphate by the cancer cell via both oxidative phosphorylation and glycolysis (33,34). The present study provides evidence that 18 F-FBnTP permits the detection of the apoptotic action of docetaxel earlier than that afforded by 18 F-FDG.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%